Analisis Dampak Kebijakan Loan To Deposit Ratio (Ldr) Terhadap Perubahan Tingkat Pengembalian Modal (Roe) - slamet heri winarno (Universitas Bina Sarana Informatika, 2017)
Measurement of health of a financial institution (bank) can be determined on several factors, including the level of liquidity and profitability. By knowing the liquidity and profitability, we can find out if a bank is still able to function as an institution intermediaris in meeting the funding needs for the community. In order to produce optimum gain level, naturally required optimal management of the funds between deposits and borrowed funds are reflected in the Loan to Deposit Ratio (LDR). Optimal management of the funds is expected to produce significant changes on the return obtained (profit) which looks at the value of Return On Equity (ROE). LDR is a measure of how much the bank's ability to refinance withdrawals and ROE is a profitability performance comparison results net profit after tax with their own capital. This study aims to analyze the impact, influence and relationships of policy Loan to Deposit Ratio (LDR) to changes in return on equity (ROE) in PT Bank Tabungan Negara (Persero) Tbk . The data used are secondary data obtained through the analysis of financial statements for the period 2004-2013. The results showed Based on hypothesis testing using correlation that produce numbers -0.890. For the calculation of the coefficient of determination obtained a value of 0.792. ROE can be explained by this equation model at 79.2%, while the remaining 20.8% is influenced by other factors. While the results of the calculation of the amount of 75.716 constant regression equation and regression coefficient of X by -0.598